DEFINING TRANSVERSAL SKILLS: PERSPECTIVES AND DEVELOPMENT - Y. Dochevska (Trakia Journal of Sciences)
The aim of the present paper is to describe international perspectives concerning terms, definitions, and meanings of transversal skills and related terminology, highlighting the skills of the future. Methods: Has been analysed the available literature and policy documents and has been implemented analysis of various sources of data via qualitative methodology and expertise of researchers. Results: Although the term transversal skills is reaching wide aspect of importance, different classifications which skills are actually considered as transversal skills are observed and vice versa – different classifications includes skills, considered as transversal ones. Conclusions: Considerations has been described in the present study aiming to stimulate reflection of stakeholders and educational experts with diverse background and to start the discussion regarding possible unification of used terminology.